(untitled) (CIPEEX, 2025)
Match Service is an innovative platform that transforms the way consumers connect with qualified service providers, making the search and hiring process more accessible and efficient. Instead of relying on traditional “word of mouth”, the site offers a digital solution that covers various areas, such as plumbing, gardening, electrical, renovations, among other specialized services. The project is guided by the need to optimize the contracting process, simplifying communication and promoting greater trust between the parties involved. By combining practicality and technology, Match Service allows users to quickly find qualified professionals, based on criteria such as location, reviews from other clients and specialization. This proposal stands out for facilitating access to quality services, while contributing to strengthening the local and regional labor market and promoting economic growth. The platform is designed to be intuitive and efficient, providing a user-friendly experience for both the client and the service provider. With just a few taps, the client can filter options and select the ideal professional for the desired task, while service providers gain visibility and more business opportunities. Match Service is also aligned with the UN’s Sustainable Development Goals, in particular number 8, which deals with decent work and sustainable economic growth. The project not only fosters economic growth by encouraging entrepreneurship and the provision of local services, but also promotes the creation of decent, productive and accessible jobs for all. By promoting an inclusive and safe environment, the platform aims to democratize access to quality services and expand job opportunities for self-employed professionals and small entrepreneurs.